Educational status of children and youth with behavioral problems in residential care - Žunić Pavlović, Vesna; Đurišić, Maša (Specijalna edukacija i rehabilitacija, 2024)
Introduction. Children and youth in foster and residential care have lower educational attainment compared to the general population. Previous research suggests that difficulties in education are especially frequent among children and youth who have been admitted to residential care due to behavioral problems. Objective. The aim of the research was to determine the educational status of children and youth who were admitted to an educational institution. Methods. The sample consisted of users who had been placed in the Institute for the Education of Children and Youth Belgrade in the previous four years (N = 69). Children and youth from the sample were of both sexes (male 75.4%), aged 9–18 years at the time of admission (AS = 15.39, SD = 2.01). Data on education and other relevant characteristics of children and youth were collected from official documentation. Results. At the time of admission, 24.6% did not attend school, and 33.2% have four or fewer grades of elementary school. During the previous education, 63.8% repeated the class, 98.2% were often absent from school, 26.1% were subjected to disciplinary measures at school, and 29.0% were educated according to an individual educational plan. Significant relationships were found between average performance and demographic characteristics of users. Conclusion. Children and youth in educational institutions experienced serious difficulties in participating and progressing in education. This research draws attention to the need for systematic monitoring and improvement of the educational attainment of children and youth in residential care in Serbia.